Fetal Ventricular Dilation; prelude to Dandy-Walker Syndrome and Hydrocephalus: Synopsis of Two Case Reports - AFODUN, Adam Moyosore; Quadri, Khadijah Kofoworola; MASUD, Mustapha Akajewole; Sheu, Sulaiman Oluwadare; Franck, Katembo Sikakulya; Okeniran, Olatayo Segun; Malinga, Raymond Joseph; Wandabwa, Julius Namasake (Nepal Journal of Neuroscience, 2022)
Accurate measurement of the 3rd and 4th ventricles is important in cases of prenatal and postnatal diagnosis of suspected cranial anomalies. Ventricular dilation occurs with excess fluid in the embryologic ventricles during brain development, we make a comparative analysis of two case reports on a 23rd-week fetus and a 10-month-old neonate. Ultrasound findings related to horns and ventricular system through transfontanelle ultrasound (excluding any > 95th error margin and < 5th percentile) can be utilized for a specific diagnosis of ventricular dilation. Hydrocephalus is defined as the accumulation of excessive CSF resulting in dilation of the cerebrospinal compartment in the calvaria; which can be acquired or congenital in origin. Hydrocephalus can also be seen due to obstructed flow, faulty absorption, and overproduction of CSF (in the subarachnoid space) by a choroid plexus papilloma. The diameter of the anterior horn of the RT and LT (hydrocephalic) lateral ventricles measured 15.3mm and 14.1mm respectively, far above the threshold for normal (control) neonates / RT and LT (anterior) lateral ventricles averaging 2.40mm and 2.51mm. These documented findings indicate the excellent agreement between fetal brain sonography in the diagnosis of fetal ventriculomegaly (anterior horn/ 10.4mm) and dilation (combined 40.8mm). Mean Head Circumference (MHC) for neonatal hydrocephalus was 44.2cm far above the normal average of 36.7cm. When we assessed the clinical benchmark of 10mm or (>19mm) for the neonate ventricle, it was far above the normal range (greater than > 95th percentile value).